2016
DOI: 10.1053/j.gastro.2016.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Multiple Dysplastic Lesions Increase Risk of Squamous Cell Carcinoma in the Esophagus, Head, and Neck

Abstract: Multiple dysplastic lesions in the esophagus increase the risk of multiple SCCs. Alcohol abstinence reduces the risk of metachronous SCCs. Clinical Trials registry: UMIN000001676 and UMIN000005466.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
160
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 165 publications
(168 citation statements)
references
References 21 publications
7
160
1
Order By: Relevance
“…This cohort study was approved by the institutional review board at each hospital; the Ethics Committee of National Hospital Organization Kurihama Medical and Addiction Center, the Ethics Committee of Kitasato University School of Medicine, the Ethics Committee of National Institute of Public Health, the Ethics Committee of National Cancer Center Hospital East, the Ethics Committee of National Cancer Center Hospital, the Ethics Committee of Hokkaido University Graduate School of Medicine, the Ethics Committee of Ishikawa Prefectural Central Hospital, the Ethics Committee of Tohoku University Graduate School of Medicine, the Ethics Committee of Shizuoka Cancer Center, the Ethics Committee of National Hospital Organization Osaka National Hospital, the Ethics Committee of Okayama University Graduate School of Medicine, Dentistry and Pharmaceutical Sciences, the Ethics Committee of Kanagawa Cancer Center, the Ethics Committee of Showa University School of Medicine, the Ethics Committee of Kumamoto Regional Medical Center, the Ethics Committee of St. Marianna University School of Medicine, the Ethics Committee of Kawasaki Municipal Hospital, the Ethics Committee of Tochigi Cancer Center, the Ethics Committee of Keio University School of Medicine, the Ethics Committee of Kyoto Prefectural University of Medicine, and the Ethics Committee of Kyoto University Graduate School of Medicine. We obtained a written informed consent from each patient (UMIN Clinical Trials Registry ID: UMIN000001676) [12]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This cohort study was approved by the institutional review board at each hospital; the Ethics Committee of National Hospital Organization Kurihama Medical and Addiction Center, the Ethics Committee of Kitasato University School of Medicine, the Ethics Committee of National Institute of Public Health, the Ethics Committee of National Cancer Center Hospital East, the Ethics Committee of National Cancer Center Hospital, the Ethics Committee of Hokkaido University Graduate School of Medicine, the Ethics Committee of Ishikawa Prefectural Central Hospital, the Ethics Committee of Tohoku University Graduate School of Medicine, the Ethics Committee of Shizuoka Cancer Center, the Ethics Committee of National Hospital Organization Osaka National Hospital, the Ethics Committee of Okayama University Graduate School of Medicine, Dentistry and Pharmaceutical Sciences, the Ethics Committee of Kanagawa Cancer Center, the Ethics Committee of Showa University School of Medicine, the Ethics Committee of Kumamoto Regional Medical Center, the Ethics Committee of St. Marianna University School of Medicine, the Ethics Committee of Kawasaki Municipal Hospital, the Ethics Committee of Tochigi Cancer Center, the Ethics Committee of Keio University School of Medicine, the Ethics Committee of Kyoto Prefectural University of Medicine, and the Ethics Committee of Kyoto University Graduate School of Medicine. We obtained a written informed consent from each patient (UMIN Clinical Trials Registry ID: UMIN000001676) [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Although treatment of early esophageal SCC by endoscopic mucosectomy has become a widespread practice in Japan and has succeeded in improving the outcome of this high-mortality cancer [35], follow-up endoscopic examinations have revealed an extremely high rate of development of metachronous SCC in the remaining esophagus and the head and neck [611]. Our recent prospective cohort study of patients who had undergone endoscopic mucosetcomy for early esophageal SCC demonstrated a strong association between the cumulative incidence of metachronous esophageal SCC and the grade of esophageal Lugol-voiding lesions (LVLs; squamous cell dysplasia) assessed by Lugol chromoendoscopy [12]. In addition, drinking cessation decreased the rate of developing metachronous esophageal SCC [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High frequency of HPV infection in multiple dysplastic lesions of smokers or alcohol users were detected [4346]. An additive impact of SNPs, HPV, smoking and alcohol consumption on risk to develop H&N cancer could be expected [4548]. …”
Section: Hpv Cigarette Alcohol Single-nucleotide Polymorphism (Snpmentioning
confidence: 99%